Peripheral nervous system in limited systemic sclerosis - D. Melchiorre; S. Guiducci; S. Generini; A. Franca Milia; D. Nosi; A. Tani; L. Ibba Manneschi; A. Del Rosso; A. Pignone; M. Matucci Cerinic (PAGEPress Publications, 2011)
Objectives. PNS is involved in Systemic Sclerosis (SSc) since the earliest phases. Our aim is to perform an ultrastructural study on skin PNS fibers in SSc. Methods. Skin biopsies were taken from forearms of 8 patients affected by limited SSc (lSSc) and 3 controls and processed for transmission electron microscopy (TEM). The semithin sections (2 mm) were observed at light microscope and optical fields were chosen for ultrathin sections (1 mm) preparation and TEM examination. Results. In lSSc skin, in the semithin sections, damaged areas are close to apparently spared areas. At TEM, in early lSSc patients, signs of inflammation and damaged microvessels are visible in derma. PNS fibers are no damaged. In advanced lSSc, fibrosis prevails on inflammation, and slight ultrastructural alterations of PNS fibers are evident in papillar derma. Conclusions. PNS lesions are different in severity in lSSc according to the disease duration, resulting more severe in advanced than in early phase.